Arithmetic textbooks of two centuries: Goals, target groups and traditional values - Bjarnadóttir, Kristín (Icelandic Journal of Education, 2015)
This article recounts a survey of six arithmetic textbooks, written in Icelandic and published in the eighteenth, nineteenth and early twentieth century, their goals, target groups, relations to each other and to European cultural currents, and the values they represent. All of them adhere to the European arithmetic tradition of the Late Middle Ages in their introduction of Indo-Arabic numerals and arithmetic methods. The two eighteenth century textbooks were the first substantial arithmetic textbooks printed in Icelandic. They were offshoots of the Enlightenment movement, deliberately published in order to raise the educational standards of Icelanders in the field of arithmetic. Their authors, Ólafur Olavius (1780) and Ólafur Stephensen and Magnús Stephensen (Ólafur Stefánsson, 1785), were educated in Copenhagen, in direct contact with the cultural currents of Northern Europe of their time; the German- Danish Enlightenment movement, based on Evangelic-Lutheran protestant heritage. While Olavius is concerned with presenting a variety of methods to solve arithmetic problems under indirect influence from Comenius, the Stephensens present strictly academic content, drawn directly from an introductory course at the University of Copenhagen. The two nineteenth century authors, Jón Guðmundsson (1841) and Eiríkur Briem (1869; 1880), were educated in Iceland only, under the influence of the champions of the Icelandic Enlightenment movement. Both of them introduced to their fellow countrymen the art of arithmetic in a rule-based way, but in the spirit of self-instruction. They made deliberate efforts to teach young people economical allocation of their resources and avoidance of squandering their income on imported luxuries. The twentieth century authors, Sigurbjörn Á. Gíslason (1911a; 1911b; 1912) and Elías Bjarnason (1927; 1929; 1939; 1940; 1941a; 1941b; 1963; 1964; 1965), lived in a society of increasing urbanism. However, they also had firm roots in the vanishing rural society, reflected in their examples and ...